Therapist’s interpersonal style and therapy benefit as the determinants of personality self-reports in clients - Hadžiahmetović, Nina; Alispahić, Sabina; Tuce, Đenita; Hasanbegović-Anić, Enedina (Vojnosanitetski pregled, 2017)
Background/Aim. In (counter)transference relationship therapist’s interpersonal style, implying the perceived relation of therapist to a client (patient) in terms of control, autonomy, care and positive feedback, has been shown to be important. The aim of our study was to assess the relationship between therapist’s interpersonal style and clients’ personality self-reports. Within therapist’s interpersonal style, preliminary validation of the Therapist’s Interpersonal Style Scale has been conducted, which included double translation method, exploratory factor analysis, confirmatory factor analysis, as well as the reliability tests of the derived components. Methods. This research was conducted on a group of 206 clients, attending one of the four psychotherapy modalities: psychoanalysis, gestalt therapy, cognitive-behavioral and systemic family therapy. Beside Therapist’s Interpersonal Style Scale, Big Five Questionnaire and Therapy Benefit Scale were administered, showing good internal consistency. Results. Principal component analysis of therapist’s interpersonal style singled out two components Supportive Autonomy and Ignoring Control, explaining 42% of variance. Two-factor model of the therapist’s styles was better fitted in confirmatory factor analysis than the original 4-factor model. Structural model showing indirect and direct effects of therapist’s interpersonal styles on self-reports in clients indicates good fitness (χ2(12) = 8.932, p = 0.709; goodness-of-fit index = 0.989), with Ignoring Control having direct effect on Stability, Supportive Autonomy on Therapy Benefit, and Therapy Benefit on Plasticity. Conclusion. The results of this study indicate the importance of further research on therapist’s interpersonal style, as well as further validation of the instrument that measures this construct. Besides, a client’s perception that the therapy is being helpful could instigate more explorative and approach-oriented behavior, what indirectly might contribute to a client’s stability.